2005
DOI: 10.1007/978-3-540-31957-3_75
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Group Key Management with Partially Trusted Controllers

Abstract: Scalable group key management solutions are crucial for supporting Internet applications that are based on a group communication model. Many solutions have been proposed and of these the most efficient and scalable ones are based on logical key hierarchies (LKH) with symmetric keys organized in a tree. However, these solutions centralize trust in the group controller and make it an attractive attack target for access to communication keys for all groups supported by the controller. In this paper we propose a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Some group key management techniques [1][2][3][4] had been proposed which are applied for various group communications in the early time. Lately, with the development of mobile ad hoc networks and wireless sensor networks, researchers found that traditional group key management schemes cannot be directly applied for the mobile ad hoc networks because of the energy-constrained feature in mobile ad hoc networks.…”
Section: Related Workmentioning
confidence: 99%
“…Some group key management techniques [1][2][3][4] had been proposed which are applied for various group communications in the early time. Lately, with the development of mobile ad hoc networks and wireless sensor networks, researchers found that traditional group key management schemes cannot be directly applied for the mobile ad hoc networks because of the energy-constrained feature in mobile ad hoc networks.…”
Section: Related Workmentioning
confidence: 99%